2017
DOI: 10.1111/jgs.15008
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi for Risk of Falls. A Meta‐analysis

Abstract: In at-risk adults and older adults, tai chi practice may reduce the rate of falls and injury-related falls over the short term (<12 months) by approximately 43% and 50%, respectively. Tai chi practice may not influence time to first fall in these populations. Due to the low quality of evidence, more studies investigating the effects of tai chi on injurious falls and time to first fall are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 45 publications
3
56
0
Order By: Relevance
“…The coordinated and balanced movements of TC promote efficiency of movement and economy of effort that is ideal for falls prevention. [6][7][8] It provides benefit for many chronic health conditions seen in older adults and offers psychological, social and health promotion benefits. 5,6 TC is a mild-to-moderate aerobic exercise depending on style (lineage) or health status of the participant.…”
Section: What Is Tai Chi?mentioning
confidence: 99%
“…The coordinated and balanced movements of TC promote efficiency of movement and economy of effort that is ideal for falls prevention. [6][7][8] It provides benefit for many chronic health conditions seen in older adults and offers psychological, social and health promotion benefits. 5,6 TC is a mild-to-moderate aerobic exercise depending on style (lineage) or health status of the participant.…”
Section: What Is Tai Chi?mentioning
confidence: 99%
“…One meta-analysis examined the effect of Tai-Chi on the incidence of falls and time to first fall in adults aged 56 to 98 years compared to usual care or other interventions in 10 randomised controlled trials 18 . Interventions were typically of 1-hour duration and delivered at a frequency of 1-3 times per week for 12-26 weeks.…”
Section: Risk Of Fallsmentioning
confidence: 99%
“…Although there is review level evidence of the benefit of multi-component exercise interventions on self-reported measures of quality of life 22 , it was not possible to separate out the independent effects of musculoskeletal fitness exercise or balance exercise. However, as part of a Cochrane review 18 of the effects of resistance training in older adults (see Physical Function section for details) one analysis compared the effects of resistance training versus a control group on the Vitality measure of the SF-36 in 10 randomised controlled trials and reported no difference between groups. In a further sub-group analysis of 2 trials, high intensity resistance training did have a positive effect on Vitality compared to low intensity training.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…18 TC includes gentle movements that may simulate activities of daily living. At least some evidence suggests TC may be effective for improving balance 19 and fall prevention, 20 congestive heart failure, 21 bone health, 22 osteoarthritis, 23,24 and depression, 25 conditions that are more common in older adults. We are unaware of studies of TC for cLBP that focused on older adults (and it is unclear if any were included in the published trials).…”
Section: Introductionmentioning
confidence: 99%